Breastfeeding mitigates the effects of maternal HIV on infant infectious morbidity in the Option B+ era. (23rd October 2018) - Tchakoute, Christophe Toukam; Sainani, Kristin Lynn; Osawe, Sophia; Datong, Pam; Kiravu, Agano; Rosenthal, Kenneth L.; Gray, Clive M.; Cameron, D. William; Abimiku, Alash'le; Jaspan, Heather B.
Abstract : Objective: The effects of in-utero HIV-exposure on infectious morbidity and mortality in settings with universal maternal treatment and high breastfeeding rates are unclear. Further, the benefits of exclusive feeding options have not been assessed in the Option B+ era. We investigated these in two African settings with high breastfeeding uptake and good HIV treatment infrastructure during the first year of life. Methods: Cox regression with time-changing variables in a birth cohort of 749 HIV-exposed uninfected and HIV-unexposed uninfected infants from Cape Town, South Africa and Jos, Nigeria. Results: There was no difference in infectious morbidity incidence between HIV-exposed uninfected and HIV-unexposed uninfected infants (hazard ratio 1.01; 95% CI 0.78–1.32) after adjusting for confounding variables. Formula-fed infants had significantly higher infectious morbidity incidence when compared with exclusively breastfed infants (hazard ratio 1.64; 95% CI 1.03–2.63) and mixed-breastfed infants (hazard ratio 1.42; 95% CI 1.00–2.02) after adjusting for potential confounding variables. There was no significant difference in mortality among HIV-exposed infants and HIV-unexposed infants during the first year of life in this cohort (2.04 versus 0.94%, P  = 0.38). Notably, exclusive breastfeeding for only 4 months had protective effects on morbidity up to 1 year. Conclusion: In settings with universal antiretroviral coverage and high breastfeeding rates, breastfeeding mitigates the effects of in-utero HIV exposure among infants during the first year of life. These findings support previous recommendations for exclusive breastfeeding among HIV-infected women and highlight the role that breastfeeding plays on the health of infants in settings where exclusive breastfeeding is not always feasible or where replacement feeding is recommended. Abstract : Supplemental Digital Content is available in the text